2023
DOI: 10.34133/research.0077
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Nanobody-Derived CD47 Theranostic Pairs in Solid Tumors

Abstract: Overexpression of CD47 is frequently observed in various types of human malignancies, inhibiting myeloid-mediated elimination of tumor cells and affecting the prognosis of cancer patients. By mapping biomarker expression, immuno-positron emission tomography has been increasingly used for patient screening and response monitoring. By immunization alpacas with recombinant human CD47, we prepared a CD47-targeting nanobody C2 and developed [ 68 Ga]Ga-NOTA-C2, followed by an exploration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…We demonstrate that magnetic beads with zwitterionic surfaces (MB3) exhibit superior performance for nanobody modification. By using the magnetic beads in our previous work, 56 additional amine functionalization and poly(acrylic acid) (PAA) coatings were performed to obtain an MB3 sample with zwitterionic surfaces. As shown by Figure S7, the protein recovery of MB3 was apparently higher than that of the commercial MB2 sample after the magnetic beads were incubated with the same amount of BSA protein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate that magnetic beads with zwitterionic surfaces (MB3) exhibit superior performance for nanobody modification. By using the magnetic beads in our previous work, 56 additional amine functionalization and poly(acrylic acid) (PAA) coatings were performed to obtain an MB3 sample with zwitterionic surfaces. As shown by Figure S7, the protein recovery of MB3 was apparently higher than that of the commercial MB2 sample after the magnetic beads were incubated with the same amount of BSA protein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To demonstrate the generality of the immobilization method, we purchased two types of magnetic beads (MB1 with NHS groups and MB2 with carboxyl groups) from different vendors. We further prepared another type of magnetic beads with zwitterionic surfaces (MB3), because many studies have demonstrated that zwitterionic surfaces can effectively reduce nonspecific adsorption of proteins. , On basis of the magnetic beads in our previous work, additional amine functionalization and poly­(acrylic acid) (PAA) coating were performed to generate a zwitterionic surface. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) were used to characterize the different samples.…”
Section: Resultsmentioning
confidence: 99%
“…Female athymic nude mice (5 week-old; GemPharmatech) and female NCG-hCD47 humanized mice (5 week-old; GemPhar- S1). 25 We used surface plasmon resonance to determine the affinities of C2 and ABDC2 to the target protein. C2 binds to human CD47, but not murine CD47, with a high K D value of 23.50 pM.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Female athymic nude mice (5 week-old; GemPharmatech) and female NCG-hCD47 humanized mice (5 week-old; GemPhar- We have developed a series of VHHs with high and specific binding affinities to human CD47, including a clone termed C2 used in the study (Figure S1). 25 We used surface plasmon resonance to determine the affinities of C2 and ABDC2 to the target protein. C2 binds to human CD47, but not murine CD47, with a high K D value of 23.50 pM.…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation